2007
DOI: 10.1007/s10310-007-0007-y
|View full text |Cite
|
Sign up to set email alerts
|

A provisional growth model with a size–density relationship for a plantation of Paraserianthes falcataria derived from measurements taken over 2 years in Pare, Indonesia

Abstract: A growth model for a plantation of Paraserianthes falcataria was provisionally derived from measurements of 32 permanent plots taken over a period of 2 years in Pare, Indonesia. This model first predicts height growth with the polymorphic site index equation. Then density-related growth and mortality, that is, diameter and stand density, are calculated to satisfy the mathematical relationship for the reciprocal and self-thinning equations, both of which were based on the maximum size-density line with the slop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Therefore, rotation age for sawntimber production might be better extended to at least 8 years old for the plantation of P. falcataria at an average site, although the additional volume growth around the rotation age seems small. This rotation age is not so much different from the conventional one adopted by Perum Perhutani in this region, where most of the plantations are managed with an 8-years rotation with 2 m · 3 m initial spacing (Kurinobu et al 2007). The conventional rotation is 1 year or possibly 2 years shorter than the optimum one, and this discrepancy might be partly due to the difference between assumed intensity of thinning and that actually practiced, or in their production purpose, which would cover core-wood and small blockboard from the smaller size of logs.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Therefore, rotation age for sawntimber production might be better extended to at least 8 years old for the plantation of P. falcataria at an average site, although the additional volume growth around the rotation age seems small. This rotation age is not so much different from the conventional one adopted by Perum Perhutani in this region, where most of the plantations are managed with an 8-years rotation with 2 m · 3 m initial spacing (Kurinobu et al 2007). The conventional rotation is 1 year or possibly 2 years shorter than the optimum one, and this discrepancy might be partly due to the difference between assumed intensity of thinning and that actually practiced, or in their production purpose, which would cover core-wood and small blockboard from the smaller size of logs.…”
Section: Resultsmentioning
confidence: 98%
“…4. The total volume and that of sawn timber were estimated using average height and dbh predicted by the growth model (Kurinobu et al 2007) under two types of initial spacing: 2 m · 3 m and 3 m · 3 m ( Table 5). The proportion of sawn timber was small at 6 years old: 9% in 2 m · 3 m spacing and 21% in 3 m · 3 m spacing, while it increased almost linearly for the successive 2 years to reach 67% in 2 m · 3 m spacing and 80% in 3 m · 3 m spacing (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bhat et al (1998) reported that, under favourable conditions, the trees can reach a height of 7 m in 1 year, 16 m in 3 years and 33 m in 9 years. Kurinobu et al (2007a) reported that P. falcataria trees in 3-5-year-old stands growing in state-owned plantations in Kediri (East Java) have a mean diameter of 11.3-18.7 cm (maximum diameter 25.8 cm) with a mean height of 11.7-20.5 m (maximum height 23.5 m).…”
Section: Growth Ratesmentioning
confidence: 99%
“…It even thrives in marginal land, where it grows symbiotically with nitrogen-fixing Rhizobium and phosphorus-promoting mycorrhizal fungi. Therefore, it is a suitable species for industrial timber estates in southeast Asian countries (Binkley et al, 2003;Shively et al, 2004;Kurinobu et al, 2007;Siregar et al, 2007). The sengon tree typically gains 7 m in height per year and reaches a mean height of 25.5 m and a bole diameter of 17 cm after 6 years.…”
mentioning
confidence: 99%